Aspidistra tripartita (Asparagaceae, Convallarioideae), a new species from Vietnam - Vislobokov, Nikolay A.; Moshkina, Natalia A.; Kuznetsova, Svetlana P.; Kuznetsov, Andrey N.; Le, Son Xuan; Romanov, Mikhail S.; Drokina, Victoria G.; Lyskov, Dmitry F.; Kopylov-Guskov, Yury O.; Nuraliev, Maxim S. (Phytotaxa, 2024)
Aspidistra tripartita, a new species of Asparagaceae, is described and illustrated. The species was discovered in 2019 in Son La Province, northern Vietnam. Aspidistra tripartita belongs to a group of species characterized by campanulate to cupulate perianth tube and deeply lobed stigma. The new species is readily distinguishable from the other species of this group by thick rhizome (more than 10.5 mm in diameter), long and narrow ensiform leaf blades (28–71.5 cm long and 2.6–3.1 cm wide), and stamens with supraconnectives.